Higher everyday functioning, lower quality of life, and home care are associated with persisting symptoms after a COVID-19 infection in German care recipients - Koch, Martin J.; Kurotschka, Peter K.; Holmer, Dagmar; Eidenschink, Christine; Dreischulte, Tobias; Hausen, Anita; Hoelscher, Michael; Janke, Christian; Kühlein, Thomas; Nassehi, Armin; Teupser, Daniel; Gensichen, Jochen; et al. (Frontiers in Public Health, 2025)
IntroductionTo date, risk factors for persisting symptoms after a COVID-19 infection have not been investigated in people needing care or support. Prior meta-analyses identified age, obesity, and female sex as risk factors for persisting symptoms after a COVID-19 infection in the general population.MethodsThis study is part of the Bavarian ambulatory COVID-19 monitor. Data were collected from ambulatory patients needing care/support and a past COVID-19 infection. Different exposure measures (age, sex, body-mass index, income, packyears, smoker status, relationship status, type of care, care level, educational and vocational qualification, quality of life, health status, functioning, depression, cognitive abilities, anxiety) and persisting symptoms after COVID-19 (≥ 1 symptom with a duration of ≥12 weeks following a COVID-19 infection) were collected. Bivariate analyses and multiple logistic regression with multiple imputations were used to investigate the association between exposure and persisting symptoms.ResultsWe included 514 participants (COVID-19 infection, needing care/support, completed questions on persistent symptoms). 68.3% were female, with a mean age of 80.5 years (range: 24–103 years). The sample is characterized by the need for support (i.e., degree of impairment of independence or frailty score ≥ 5). Bivariate analyses revealed associations of everyday functioning, depression, cognitive functioning, living in a relationship, care level, educational qualification, vocational qualification, and type of care with persisting symptoms. In multiple logistic regression, a higher level of functioning (OR = 2.72, 95%-CI: 1.20, 6.17), the quality of life (OR = 1.12, 95%-CI: 1.03, 1.23), and the type of care (OR = 3.16, 95%-CI: 1.48, 6.73) were significantly associated with persisting symptoms.DiscussionThis is one of the first studies investigating the risk factors for persisting symptoms after COVID-19 in people in need of care or support. The risk factors in our study (everyday functioning, depression, cognitive functioning, living in a relationship, care level, educational qualification, vocational qualification, and type of care) differ from those identified in prior meta-analyses on the general population (age, obesity, female sex; these were not significant in our study). Our study highlights the importance of considering vulnerable groups in particular from the outset of future pandemic or epidemic events.